Educational inequalities in cervical cancer screening participation in 24 European countries - Altová, A; Kulhánová, I; Reisser, K; Netrdová, P; Brož, J; Eikemo, T A; Balaj, M; Lustigová, M (Public health, 2024)
OBJECTIVES: Cervical cancer screening (CCS) is an important public health measure for early detection of cervical cancer and prevents a large proportion of cervical cancer deaths. However, participation in CCS is relatively low and varies substantially by country and socio-economic position. This study aimed to provide up-to-date participation rates and estimates on educational inequalities in CCS participation in 24 European countries with population-based CCS programmes. STUDY DESIGN: This was a cross-sectional study. METHODS: Using data from the European Health Interview Survey (EHIS) conducted in 2019, 80,479 women aged 25-64 years were included in the analyses. First, standardized participation rates and standardized participation rates by educational attainment were calculated for all 24 countries based on each country-specific screening programme organization. Second, a series of generalized logistic models was applied to assess the effect of education on CCS participation. RESULTS: Screening participation rates ranged from 34.1% among low-educated women in Romania to 97.1% among high-educated women in Finland. We observed that lower-educated women were less likely to attend CCS than their higher-educated counterparts. Largest educational gaps were found in Sweden (odds ratio [OR] = 6.36, 95% confidence interval [CI] = 3.89-10.35) and Poland (odds ratio = 5.80, 95% CI = 4.34-7.75). CONCLUSION: Population-based screening initiatives have successfully reduced participation differences between women with medium and high educational attainment in some countries; however, persistent disparities still exist between women with low and high levels of education. There is an urgent need to increase participation rates of CCS, especially among lower-educated women.
Keywords: Education; Humans; lidé středního věku; disparity zdravotní péče; socioekonomické faktory; Cervical cancer; Female; dospělí; nádory děložního čípku; Early Detection of Cancer; lidé; Europe; Attendance; Healthcare Disparities; Socioeconomic Factors; časná detekce nádoru; Adult; ženské pohlaví; Middle Aged; Screening; Inequalities; Uterine Cervical Neoplasms; Cross-Sectional Studies; stupeň vzdělání; průřezové studie; Educational Status; Evropa